Electroactive polymeric material with condensed structure on the basis of magnesium(II) polyporphine - Vorotyntsev, Mikhail A.; Konev, Dmitry V.; Devillers, Charles H.; Bezverkhyy, Igor; Heintz, Olivier (Electrochimica acta, 2011)
Previous publication of the authors presented evidences that electrochemical oxidation of Mg(II) porphine (fully unsubstituted porphyrin, MgP) in acetonitrile (AN) at a very low potential leads to deposition of films at electrode surface corresponding to typical electroactive polymers, with their reversible transition between the electron-conducting and insulating states depending on the electrode potential/oxidation level (“film of type I”). It is demonstrated in the actual publication that these films in contact with a monomer-free solution are subject to an irreversible transformation to quite a different material (“film of type II”) under the influence of a higher positive potential (above 0.5–0.6 V vs. Ag/Ag + in AN). Films with the same properties may also be obtained directly by electrooxidation of the monomer, MgP, at a sufficiently high potential. Films of type II possess a high redox activity and electronic conductivity within the whole potential interval of above 3 V in the width. Their grayish color is related to a constant absorption intensity within the whole range of wavelengths studied (320–1000 nm). On the basis of a combination of experimental observations (ATR IR and XPS) and literature data the molecular structure of this new material is assumed to be polymer chains of directly linked porphine units (with a partial loss of Mg cations), probably with multiple bonds ( meso– meso and β– β types) between neighboring units.